2013
DOI: 10.1186/1475-2840-12-41
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of metabolic syndrome on subclinical atherosclerosis according to the presence of diabetes

Abstract: BackgroundMetabolic syndrome (MS) is associated with increased risks of diabetes and atherosclerotic cardiovascular disease. However, data on the impact of MS and its individual components on subclinical atherosclerosis (SCA) according to diabetes status are scarce.MethodsSurrogate markers of SCA, brachial–ankle pulse wave velocity (baPWV), and carotid intima–medial thickness (IMT) and plaque were assessed in 2,560 subjects (60 ± 8 years, 33% men) who participated in baseline health examinations for a communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
1
35
0
1
Order By: Relevance
“…Park et al suggested that TyG index was an effective marker for early detecting subclinical coronary atherosclerosis even in the absence of traditional CV risk factors [40]. However, considering the inconsistent results for the association of metabolic syndrome with ASCVD in diabetic patients [41,42], further large prospective investigation for the clinical significance of TyG index in established diabetes should be necessary in diverse ethnic population.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al suggested that TyG index was an effective marker for early detecting subclinical coronary atherosclerosis even in the absence of traditional CV risk factors [40]. However, considering the inconsistent results for the association of metabolic syndrome with ASCVD in diabetic patients [41,42], further large prospective investigation for the clinical significance of TyG index in established diabetes should be necessary in diverse ethnic population.…”
Section: Discussionmentioning
confidence: 99%
“…Although its biomechanical stimuli also promotes atherogenetic changes, especially at branch points and curves 38) , the current findings indicate that ba-PWV is more influenced by elevated blood pressure than max- participant. Although this assessment was adopted in some previous studies [45][46][47][48][49][50][51] ; others assessed ba-PWV as the mean of the two measurements [52][53][54] or the measurement on one specific side (e.g., the right side) 55,56) . Future studies will be needed to investigate whether similar findings would be obtained when these assessments were used instead of selecting the higher value.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia, as one of the components of the MS, is closely related to a constellation of metabolic risk factors including a central distribution of adiposity or visceral obesity, insulin resistance, impaired glucose tolerance, hypertension, and high TG and/or low HDL-C, associated with an atherogenic, procoagulant, and proinflammatory state [56][57][58][59][60][61][62][63][64].…”
Section: Hypertriglyceridemia As a Major Component Of Atherogenic Dysmentioning
confidence: 99%